Avaliação das armadilhas MosquiTRAP, BG-Sentinel e BG-Mosquitito como possíveis ferramentas no controle de Aedes aegypti - Carolin Marlen Degener (2014)
In the first three chapters of the present thesis, the BG-Sentinel (BGS), the MosquiTRAP (MQT) and the BG-Mosquitito (BGM) mosquito traps, designed for Aedes aegypti (L.) monitoring, were evaluated for their use as dengue vector control tools in mass trapping experiments. In the fourth chapter, longitudinal monitoring data of BGSs and MQTs were compared and associations between trap catches, dengue incidence and meteorological variables were analyzed. The first experiment evaluated the effect of mass trapping with BGSs on adult populations of dengue vectors in Manaus (AM). Results of entomological monitoring indicate that mass trapping significantly reduced the abundance of adult females Ae. aegypti during the first five rainy months of the study, but not during the dry season. In the subsequent rainy season, less females were caught in the treated areas, however without significant difference in comparison to the control arm. The serological study for the presence of DENV specific IgM antibodies indicated, that recent dengue infections were less frequent in the mass trapping arm, but the difference in comparison to the control arm was not significant. The results were not completely conclusive but there is evidence that the BGS is a promising tool that might be used as a part of dengue control programs. However, additional studies are necessary to prove a significant effect of BGS mass trapping on vector abundance and dengue virus transmission. In the second chapter, MQTs were evaluated as a dengue vector control tool in Manaus. Significantly more female Ae. aegypti were present in the treated areas during the intervention, in comparison to the untreated control areas. Therefore, entomological monitoring suggested that MQT mass trapping did not reduce the abundance of adult dengue vectors. The frequency of recent dengue infections was not reduced in the mass trapping arm. According to the results of this study there is no evidence that MQT mass trapping (using three traps per house) might be used as a part of dengue control programs in Manaus. Therefore, the use of MQT is only recommendable for Ae. aegypti monitoring. In the third experiment, mass trapping with BGMs was used in a neighborhood of Sete Lagoas (MG) with high infestation of Ae. aegypti, according to the Intelligent Dengue Monitoring (MI-D). Monitoring was performed using MQTs e BGMs. Results of MQT monitoring revealed that there were significantly less gravid Ae. aegypti in the mass trapping area. The BGM monitoring traps however suggested no significant difference between the adult female dengue vector catches in the two areas. The results indicate, that BGMs might be used as a part of dengue control strategies in combination with MI-D. Additional studies are necessary to prove a significant effect of the traps. The objectives of the study described in chapter IV were to compare mosquito collections of two trap types, to characterize temporal changes of the mosquito population and to investigate the influence of meteorological variables on mosquito collections. Additionally, associations between adult mosquito collections and dengue incidence were analyzed. Correlation between mean monthly Ae. aegypti collections and monthly dengue incidence was moderate negative for MQT and moderate positive for BGS. The two traps revealed differing temporal infestation patterns, with highest mosquito collections of MQTs during the dry season and highest collections of BGSs during the first rainy season. Both traps were sensitive to detect the presence of dengue vectors in all monitoring weeks. Several meteorological variables were significant predictors of mosquito collections in BGS, but for MQT, only the number of rainy days in the previous week was significant. The findings help to understand the effects of meteorological variables on mosquito infestation indices of two different traps for adult dengue vectors in the climatic conditions of Manaus.